Dynamics of palm collections (Arecaceae) in the Bogor Botanic Garden in periods 1957-2019 - Rizmasari, Alifta Dina Lutvia; Wahidah, Baiq Farhatul; Witono, Joko Ridho (Buletin Kebun Raya, 2023)
Bogor Botanical Garden conserves various species of palm species originating from Indonesia and overseas. As one of the flagship collections, the number of genera, species, and specimens fluctuates from time to time. This study aimed to determine the dynamics of palm collections (Arecaceae) in the Bogor Botanical Garden after independence in the period 1957–2019. Data collection was carried out by direct observation of palm collections in the garden, checking collection catalog books and databases, and also reviewing various relevant literature. The results showed that the collection of Arecaceae in the Bogor Botanical Garden from 1957 to 2019 consisted of 129 genera, 554 species, and 3.652 specimens. In the 1957 catalog, there were 91 genera, 271 species, and 870 specimens. In the 2019 catalog, there were 78 genera, 241 species, and 1.009 specimens consisting of 38 genera and 99 species originating from Indonesia, while the number of palm collections originating from other countries was 52 genera and 139 species. In general, the number of genera and species of palm in the Bogor Botanical Garden has decreased by as much as 13 genera and 29 species. Several internal factors, such as old and fallen palms, and also external factors, such as disturbances by pests and diseases. The selection of palm sites suitable for climatic and environmental conditions and intensive maintenance in the Bogor Botanical Garden is essential for optimal growth and reducing the potential death in the garden.